80th Anniversary of G.I. Muromtsev - - - (RUDN Journal of Law, 2016)
The material focuses to the 80th anniversary of Doctor of Law, Professor of the Department of the Theory of Law and State, Law Institute of the People’s Friendship University of Russia G.I. Muromtsev, a specialist in the filds of theory of state and law, law of developing countries, comparative study of legal cultures.